Validation of the Chinese Version of KIDSCREEN-10 Quality of Life Questionnaire: A Rasch Model Estimation - Gong, Zepeng; Xue, Jia; Han, Ziqiang; Li, Yuhuan (Frontiers in Psychology, 2021)
The KIDSCREEN-10 was deemed as a cross-national instrument for measuring Health-Related Quality of Life (HRQoL). However, no empirical endeavor has explored its reliability and validity in the context of China. This study aims to translate and validate the Chinese version of the KIDSCREEN-10 questionnaire. The KIDSCREEN-10 was translated into Chinese (Mandarin) using a blindly bilingual forward-backward-forward technique. A cross-sectional survey includes 1,830 students aged from 8 to 18 years was conducted in a County located in Gansu province, China. Psychometric properties were evaluated using the Rasch partial credit model, ANOVA analysis, and the correlation analysis. Results indicated that the KIDSCREEN-10 performed good internal consistency, known group validity, and concurrent validity, but there were still some deficiencies in psychometrics: first, disordered response categories were found between category 2 (seldom) and 3 (sometimes); second, item 3 (“Have you felt sad?”), 4 (“Have you felt lonely?”), and 5 (“Have enough time for self?”) demonstrated misfit to the Rasch model; third, item 3 and 4 exhibited differential item functioning. After collapsing the disordered response categories and removing the three misfit items, the seven-item questionnaire performed good psychometric properties. However, the seven-item version doesn’t cover the psychological well-being dimension of HRQoL, and that may lead to inappropriate measures of HRQOL. Therefore, this paper suggested to use classical test theory to investigate the psychological properties of the KIDSCREEN-10.